Replication Data for: Using subsidised seed to catalyse demand-driven bean seed systems in Malawi - Rubyogo, Jean-Claude; Magreta, Ruth; Kambewa, Dymon; Chirwa, Rowland; Mazuma, Elisa; Andrews, Martin (International Center for Tropical Agriculture, 2016)
Through an innovative public-private partnership, Demeter Agricultural Limited, along with the Malawi National Bean Programme and the International Center for Tropical Agriculture, supplied 2,559 tons of certified bean seed between 2009 and 2012 through the government's Targeted Farm Input Programme. Farmers were satisfied with the variety supplied, timeliness of the operation, pack size, and information provided. Growing numbers also accessed new improved varieties, from 264,661 households in 2009 to 344,200 in 2012. These emerging farmers’ demands and the subsequent DAL responses suggest a base for building sustainable delivery systems. However, decentralised seed-based systems will be needed for promoting varieties suited to micro-ecological niches.